Directly diode and bi-directional pumping 6 kW continuous-wave all-fibre laser. (17th October 2018) - Xiao, Qirong; Li, Dan; Huang, Yusheng; Wang, Xuejiao; Wang, Zehui; Tian, Jiading; Yan, Ping; Gong, Mali
Abstract: In this paper, a 6 kW continuous-wave all-fiber laser by direct 975 nm diode pumping is reported. The unique part of this system is the usage of non-wavelength-stabilized laser diodes in a bidirectional pumping configuration. The bidirectional pumping configuration not only increases the pumping power, but also shortens the fiber length and thus, restricts the nonlinear Raman effect. The fiber laser emits a maximum output power of 6020 W at a wavelength of 1070.1 nm without reaching the Raman threshold. With a corresponding optical-to-optical efficiency of 76.5%, ASE and Raman suppression of 25 dB could be reached. No transverse mode instability occurred during the experiment, and the power stability was measured to be within 2.5%@5260 W during a 1 h continuous operation test.